Estimation of the burden of shielding among a cross-section of patients attending rheumatology clinics with SLE—data from the BSR audit of systemic lupus erythematosus. (14th October 2020) - Rutter, Megan; Lanyon, Peter C; Sandhu, Ravinder; Batten, Rebecca L; Garner, Rozeena; Little, Jayne; Narayan, Nehal; Sharp, Charlotte A; Bruce, Ian N; Erb, Nicola; Griffiths, Bridget; Guest, Hannah; et al.
Abstract: Objectives: We aimed to estimate what proportion of people with SLE attending UK rheumatology clinics would be categorized as being at high risk from coronavirus disease 2019 (COVID-19) and therefore asked to shield, and explore what implications this has for rheumatology clinical practice. Methods: We used data from the British Society for Rheumatology multicentre audit of SLE, which included a large, representative cross-sectional sample of patients attending UK Rheumatology clinics with SLE. We calculated who would receive shielding advice using the British Society for Rheumatology's risk stratification guidance and accompanying scoring grid, and assessed whether ethnicity and history of nephritis were over-represented in the shielding group. Results: The audit included 1003 patients from 51 centres across all 4 nations of the UK. Overall 344 (34.3%) patients had a shielding score ≥3 and would have been advised to shield. People with previous or current LN were 2.6 (1.9–3.4) times more likely to be in the shielding group than people with no previous LN ( P < 0.001). Ethnicity was not evenly distributed between the groups (chi-squared P < 0.001). Compared with White people, people of Black ethnicity were 1.9 (1.3–2.8) and Asian 1.9 (1.3–2.7) times more likely to be in the shielding group. Increased risk persisted after controlling for LN. Conclusion: Our study demonstrates the large number of people with SLE who are likely to be shielding. Implications for clinical practice include considering communication across language and cultural differences, and ways to conduct renal assessment including urinalysis, during telephone and video consultations for patients who are shielding.